2017
DOI: 10.1111/1467-8268.12257
|View full text |Cite
|
Sign up to set email alerts
|

Dividend Policy and Shareholders’ Value: Evidence from Listed Companies in Ghana

Abstract: This study examines the effect of dividend policy on shareholder value of listed companies in Ghana. It analyses the factors affecting dividend policy and how dividend policy affects shareholders’ value. Data from 2009 to 2014 financial reports of listed companies on the Ghana Stock Exchange were used. The data was analysed using pooled OLS panel regression. The findings reveal that ROE, firm age, tax, tangibility, GDP growth and interest rate are statistically significant in explaining dividend policy. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 25 publications
3
36
0
Order By: Relevance
“…Ofori‐Sasu et al . () examined the effect of the dividend policy decision on shareholders’ value of listed companies in Ghana using market value per share held by shareholders, and they found that dividend per share improved shareholders’ value of listed firms in Ghana.…”
Section: Empirical Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…Ofori‐Sasu et al . () examined the effect of the dividend policy decision on shareholders’ value of listed companies in Ghana using market value per share held by shareholders, and they found that dividend per share improved shareholders’ value of listed firms in Ghana.…”
Section: Empirical Literaturementioning
confidence: 99%
“…Dividend policy decision has been an important predictive power used to forecast the wealth of shareholders (Ofori‐Sasu et al ., ). Board structure, which involves the collective role of board members and board characteristics, influence dividend payout decision and also builds investors’ confidence (Fuzi et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Moreoover, the bulk of recent financial development literature on Africa has not focused on market power in the banking industry(Daniel, 2017;Fowowe, 2014;Wale & Makina, 2017;Chikalipah, 2017;Bocher et al, 2017;Osah & Kyobe, 2017; Oben & Sakyi, 2017;Ofori-Sasu et al, 2017;Chapoto & Aboagye, 2017; Iyke & Odhiambo, 2017;Boadi et al, 2017).…”
mentioning
confidence: 99%